Kinetics of Lime-Enhanced Hydrogen Reduction of Solid Nickel Sulphide - Pathak R.; Mankhand T.R.; Kachhawaha J.S.; Prasad P.M. (My University, 2025)
Investigations have been carried out on the hydrogen reduction of solid nickel sulphide (Bi-Ni3S2) in the presence of lime. The effects of the charge composition, temperature (500-700°C). hydrogen flow rate, time of reduction and particle size of the sulphide have been studied. Lime was found to tremendously enhance the reduction process and drastically stifle H2S emission into the off-gas. Temperature as well as hydrogen flow rate were found to affect the reduction process and best results were achieved (in static bed experiments) with 200% CaO addition at 630°C in 2 hr employing a hydrogen flow rate of 0.2 l/min. Thermodynamic considerations and several experimental findings indicate that the progress of the Ni3S2-CaO-H2 reaction is governed by the intrinsic kinetics of the Ni3S2-H2 reaction. Kinetic analysis reveals the observance of Jander's linear rate equation indicative of phase boundary control at the sulphide/gas interface. Scanning electron microscopic studies on the reduced nickel sulphide pellets show that like in solid state transformations, discontinuous precipitation (cellular morphology) is exhibited. © 1992, Taylor & Francis Group, LLC. All rights reserved.